Development of a European harmonised standard to determine the natural radioactivity concentrations in building materials. (20th May 2018) - With, G. de; Michalik, B.; Hoffmann, B.; Döse, M.
Highlights: A European harmonized standard for the determination of 226 Ra, 232 Th and 40 K in building materials. The standard considers existing regulations and standardized practices, such as ISO and NEN. The method is applicable to samples from products as well as its individual material constituents. Abstract: In 2013 the European Commission has published its latest basic safety standards for protection against the dangers arising from exposure to ionising radiation (Council Directive 2013/59/Euratom). The council directive regulates radiation exposure from building materials through the presence of radioactivity ( 226 Ra, 232 Th and 40 K) in these materials. Pivotal to successful regulation is the availability of a harmonised test method for the determination of the radionuclide concentrations as these nuclides form the basis for dose assessment and compliance. In 2017 a Technical Specification (CEN, 2017) on the determination of the activity concentrations of 226 Ra, 232 Th and 40 K in construction products was published by the European Committee for Standardization (CEN). The purpose of this work is to give an outline of the proposed method, with the protocols for sampling, measurement and data processing as well as a summary of the robustness testing and the expert comments that have been received following the final consultation.